Hepatokine α1-Microglobulin Signaling Exacerbates Inflammation and Disturbs Fibrotic Repair in Mouse Myocardial Infarction. Issue 1 (December 2018) - Hakuno, Daihiko; Kimura, Masahiro; Ito, Shinji; Satoh, Junko; Nakashima, Yasuhiro; Horie, Takahiro; Kuwabara, Yasuhide; Nishiga, Masataka; Ide, Yuya; Baba, Osamu; Nishi, Hitoo; Nakao, Tetsushi; et al.
Abstract Acute cardiac rupture and adverse left ventricular (LV) remodeling causing heart failure are serious complications of acute myocardial infarction (MI). While cardio-hepatic interactions have been recognized, their role in MI remains unknown. We treated cultured cardiomyocytes with conditioned media from various cell types and analyzed the media by mass spectrometry to identify α1-microglobulin (AM) as an Akt-activating hepatokine. In mouse MI model, AM protein transiently distributed in the infarct and border zones during the acute phase, reflecting infiltration of AM-bound macrophages. AM stimulation activated Akt, NFκB, and ERK signaling and enhanced inflammation as well as macrophage migration and polarization, while inhibited fibrogenesis-related mRNA expression in cultured macrophages and cardiac fibroblasts. Intramyocardial AM administration exacerbated macrophage infiltration, inflammation, and matrix metalloproteinase 9 mRNA expression in the infarct and border zones, whereas disturbed fibrotic repair, then provoked acute cardiac rupture in MI. Shotgun proteomics and lipid pull-down analysis found that AM partly binds to phosphatidic acid (PA) for its signaling and function. Furthermore, systemic delivery of a selective inhibitor of diacylglycerol kinase α-mediated PA synthesis notably reduced macrophage infiltration, inflammation, matrix metalloproteinase activity, and adverse LV remodeling in MI. Therefore, targeting AM signaling could be a novel pharmacological option to mitigate adverse LV remodeling in MI.